2018
DOI: 10.1155/2018/4127108
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Surface-Enhanced Raman Scattering Substrates Based on Immobilized Silver-Capped Nanoparticles

Abstract: Novel results concerning surface-enhanced Raman scattering mediated by thiol-immobilized capped silver nanoparticles attached to a silicon Si(100) substrate are presented. The attachment of the nanoparticles is achieved by chemically modifying the surface of Si(100) in order to provide sulfhydryl groups covalently linked to the substrate and then covering these surfaces with bare and polymer-capped silver nanoparticles. The modified silicon substrate, the nanoparticles, and the sensors are characterized by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
(52 reference statements)
0
9
1
Order By: Relevance
“…The relative standard deviation (RSD) of these EC-SERS intensities was calculated to be 1.41%. Compared with other studies [ 36 , 37 , 38 ], the RSD value obtained here is very low, which indicates that the SERS enhancement of the developed EC-SERS chip is quite uniform and suite for quantitative measurement. In addition, compared with the SERS chip, the integrated EC-SERS chip can directly detect the analyte solution without waiting for it to dry on the SERS chip.…”
Section: Resultscontrasting
confidence: 76%
“…The relative standard deviation (RSD) of these EC-SERS intensities was calculated to be 1.41%. Compared with other studies [ 36 , 37 , 38 ], the RSD value obtained here is very low, which indicates that the SERS enhancement of the developed EC-SERS chip is quite uniform and suite for quantitative measurement. In addition, compared with the SERS chip, the integrated EC-SERS chip can directly detect the analyte solution without waiting for it to dry on the SERS chip.…”
Section: Resultscontrasting
confidence: 76%
“…relative standard deviation (RSD) of intensities of the 1503 cm −1 Raman characteristic peak was calculated to be 7.28%, which is relatively low compared to other studies [25][26][27], indicating good uniformity and reproducibility of the fabricated SERS substrates. Internsity (a.u.…”
Section: Performance Of the Sers Substratesmentioning
confidence: 61%
“…The SERS intensities of the Raman characteristic peak of the 1503 cm −1 band from these locations are further displayed in Figure 10b. The relative standard deviation (RSD) of intensities of the 1503 cm −1 Raman characteristic peak was calculated to be 7.28%, which is relatively low compared to other studies [25][26][27], indicating good uniformity and reproducibility of the fabricated SERS substrates. characteristic peak of the 1503 cm band from these locations are further displayed in Figure 10b.…”
Section: Performance Of the Sers Substratesmentioning
confidence: 63%
“…Recently, various metal nanoparticles with different shapes have provided unique plasmonic behavior to construct SERS-based biosensors [ 23 ]. For example, it was reported that through an enhancement of Au nanorods a Raman signal could be elucidated by longitudinal and transverse plasmon bands, an effect which had not been observed in spherical Au nanoparticles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%